Age-dependent nuclear lipid droplet deposition is a cellular hallmark of aging in Caenorhabditis elegans. - Palikaras, Konstantinos; Mari, Meropi; Ploumi, Christina; Princz, Andrea; Filippidis, George; Tavernarakis, Nektarios (Aging Cell, 2023)
Aging is the major risk factor for several life-threatening pathologies and impairs the function of multiple cellular compartments and organelles. Age-dependent deterioration of nuclear morphology is a common feature in evolutionarily divergent organisms. Lipid droplets have been shown to localize in most nuclear compartments, where they impinge on genome architecture and integrity. However, the significance of progressive nuclear lipid accumulation and its impact on organismal homeostasis remain obscure. Here, we implement non-linear imaging modalities to monitor and quantify age-dependent nuclear lipid deposition in Caenorhabditis elegans. We find that lipid droplets increasingly accumulate in the nuclear envelope, during aging. Longevity-promoting interventions, such as low insulin signaling and caloric restriction, abolish the rate of nuclear lipid accrual and decrease the size of lipid droplets. Suppression of lipotoxic lipid accumulation in hypodermal and intestinal nuclei is dependent on the transcription factor HLH-30/TFEB and the triglyceride lipase ATGL-1. HLH-30 regulates the expression of ATGL-1 to reduce nuclear lipid droplet abundance in response to lifespan-extending conditions. Notably, ATGL-1 localizes to the nuclear envelope and moderates lipid content in long-lived mutant nematodes during aging. Our findings indicate that the reduced ATGL-1 activity leads to excessive nuclear lipid accumulation, perturbing nuclear homeostasis and undermining organismal physiology, during aging.